Neural Control of Inflammation: Implications for Perioperative and Critical Care. (May 2016) - Steinberg, Benjamin E.; Sundman, Eva; Terrando, Niccolo; Eriksson, Lars I.; Olofsson, Peder S.
Abstract : Inflammation and immunity are regulated by neural reflexes. Recent basic science research has demonstrated that a neural reflex, termed the inflammatory reflex, modulates systemic and regional inflammation in a multiplicity of clinical conditions encountered in perioperative medicine and critical care. In this review, the authors describe the anatomic and physiologic basis of the inflammatory reflex and review the evidence implicating this pathway in the modulation of sepsis, ventilator-induced lung injury, postoperative cognitive dysfunction, myocardial ischemia–reperfusion injury, and traumatic hemorrhage. The authors conclude with a discussion of how these new insights might spawn novel therapeutic strategies for the treatment of inflammatory diseases in the context of perioperative and critical care medicine. Abstract : Neural reflexes modulate systemic inflammation in clinical conditions encountered in perioperative and critical care. This review discusses how recent studies in this area are leading to new therapeutic strategies for the treatment of inflammatory diseases.